Computer Animation Marvels ((Mind's Eye))
Compilación de diecisiete cortometrajes de animación por computadora, producidos con propósitos artísticos y/o didácticos: Pets; The Persecution; Vache Folle; Ticked Off; Carved Journey; The Hungry One; The Physics of Cartoons, part 1; H2O; Botlie Blues; CPU; Last Call; rockpaperscissors; A Narrow Martian of Error; Love and Rockets; Fly Hard; The Sitter y Bingo.